Air Quality Characteristics in Junior High School Classroom with Natural Ventilation in Pangkep Regency - Nur Mutmainnah; Rosady Mulyadi; Baharuddin Hamzah (EPI International Journal of Engineering, 2019)
The indoor air quality room has turned out to be a major concern due to its adverse effects on human health. This is related to the level of activity of human spend almost 90 percent of their time indoors. This study aims to identify the characteristics of air quality in classrooms with natural ventilation systems in three different schools which vary in topography and the surrounding environment, namely coastal areas, lowlands, and mountains. Air quality measurement focuses on CO, CO2 concentration, total dust content, temperature, humidity, and airflow velocity. The statistical results showed significantly different (p <0.05) in air quality parameters among those three schools. The CO and CO2 concentrations in the three schools are below the recommendations required by DOSH and ASHRAE. This clarifies that a well-used of a natural ventilation system is able to maintain the air quality in the classroom. The measurement of total dust levels was above the threshold required by the Ministry of Health of the Republic of Indonesia No.1405/MENKES/SK/XI/2002. In addition, there was a significant relationship (p <0.05) between air pollutants and meteorological factors such as temperature and air humidity in the classroom. The study found that there was an influence of human activity level and the surrounding environment on the amount of pollutants concentration in the classroom.